(untitled) (KYAMC Journal, 2021)
Background: Globus pharyngeus or feeling of a lump in the throat is a very common complaint in patients visiting the otolaryngology outpatient department. Pharmacotherapy with low dose amitriptyline has a significant effect in relieving the symptoms, although success rate varies among patients. Objectives: Aim for this study was to find out the benefits of low dose amitriptyline therapy in the management of Globus pharyngeus on a short term basis. Materials & Methods: This is an observational study conducted from Jan 2019 to Jan 2020. Total 50 patients were included in this study. Inclusion criteria were – subjective feeling of a lump in the throat persisting for more than 2 months, Clinical oral examination and Upper GI endoscopy revealed normal findings, age between 18–60 years of both sexes. All the patients were prescribed with 10mg Amitriptyline per oral at night for 2 months, and patients were followed during the course of treatment to assess relief of symptoms and to evaluate any side effects. Results: In this study male to female ratio was 1:4. Mean age of study group was 42.66 (_ 4.78) years. Symptomatic relief occurred in 37 (74%) patients. Increased somnolence was found in 21 patients (42%) during first 2 weeks of treatment, No improvement occurred in 8 patients (16%), and worsening of symptom occurred in 5 patients (10%). Conclusion: Low dose Amitriptyline is effective in alleviating symptoms of globus pharyngeus in most patients on a short-term basis. Although some minor side effects can occur, these are manageable. KYAMC Journal.2021;12(02): 75-77